2022
DOI: 10.1001/jamanetworkopen.2022.17633
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Hearing Loss and Hearing Aid Use Among Adults in France in the CONSTANCES Study

Abstract: Key Points Question What is the prevalence of hearing loss and hearing aid use at the population level in France? Findings In this cohort study including 186 460 French volunteers aged 18 to 75 years with audiometric data, 25% had hearing loss and 4% had disabling hearing loss. Among participants with disabling hearing loss, 37% reported using hearing aids. Meaning The findings suggest that hearing loss is prevalent among French … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…But, there are both similarities and differences to the latest nationally-representative prevalence data in comparable countries. For instance, for the "CONSTANCES" study in France, which were collected between 2011 and 2019, the prevalence-by-age curve for males closely matches those that from the NSH, but for females, the French values are almost 10% greater than the NSH's for 50's and 60's(Lisan et al, 2022). The resulting uncertainty as to which way the prevalence of hearing loss in the UK has actually changed since the 1980s emphasises the paucity of current epidemiological data(Whitty, 2023) and indicates that a suitable new UK national study of hearing needs be considered.…”
mentioning
confidence: 89%
“…But, there are both similarities and differences to the latest nationally-representative prevalence data in comparable countries. For instance, for the "CONSTANCES" study in France, which were collected between 2011 and 2019, the prevalence-by-age curve for males closely matches those that from the NSH, but for females, the French values are almost 10% greater than the NSH's for 50's and 60's(Lisan et al, 2022). The resulting uncertainty as to which way the prevalence of hearing loss in the UK has actually changed since the 1980s emphasises the paucity of current epidemiological data(Whitty, 2023) and indicates that a suitable new UK national study of hearing needs be considered.…”
mentioning
confidence: 89%
“…Germany has a prevalence of 16-25% in systematic literature searches 8 . A cohort study in France estimated the prevalence among 18-to 75-year-olds to be 25% 9 . In India, metaanalyses reported a prevalence of hearing loss ranging from 6 to 26.9% 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Chien and Lin [ 9 ] estimated that one in seven Americans over the age of 50 who have hearing loss use hearing aids. In a recent large cohort study of French adults, only 37% of people with hearing loss reported using hearing aids [ 10 ]. In Belgium, 38% of adults aged 80 and over with moderate hearing loss are underserved in the hearing care [ 11 ].…”
Section: Introductionmentioning
confidence: 99%